The Influence of Polylactide Addition to The Performance of LifePO4/C Composite as Cathode Materials - Indra Gunawan; Deswita; Heri Jodi; Wahyudianingsih (Green Engineering Society, 2023)
The polylactide and carbon addition to LiFePO4 has been studied to investigate the behavior of LiFePO4/C composite. The cathode material of LiFePO4 was prepared by coprecipitation of LiOH.H2O, (NH4)2HPO4, and FeSO4.7H2O solution. The resulting LiFePO4 was mixed with biodegradable polymer PLA in the concentration of 6, 8, 10, and 12 % weight of the polymer. Heat treatment was done by heating the precursor at 700 o C for 4 hours. The physical chemistry properties of cathode materials were analyzed by using Simultaneous Thermal Analysis (STA), X-Ray Diffractometer (XRD), Scanning Electron Microscope (SEM), and Particle Size Analyzer (PSA) methods. High Precision LCR-meter was used to perform conductivity measurement, in which the LiFePO4/C powder samples were prepared by using a 200 kg/cm2 hydraulic press. TG analysis informs gradual weight decrease at LiFePO4 temperature formation of 470 C and pyrolisis of remaining PLA occurs at 600 C. From all samples, XRD data indicate the pure phase of LiFePO4. SEM image shows the uniform distribution particle of the sample with 6 % PLA content with a conductivity of 1.99 X 10-2 Scm-1.